Rarely are dedicated to investigating (Journal of Parents and Teachers, 2014)
Only a few times we work as investigators and this happens because of five main reasons: not realizing something, letting things flow, blame others, discouragement and having good intentions. This is why this article suggests two investigation models: the centripetal investigation in which one starts by the last consequence of an event; and the centrifuge spiral in which a hypothesis is created and related to its consequences. Finally, the articles ends talking about some examples of good investigations carried out by some institutions related to teaching.
Keywords: investigation; educative investigation; presentation; centripetal spiral; centrifuge spiral.; creative